Anterior Segment Optical Coherence Tomography of Post-Descemet Stripping Automated Endothelial Keratoplasty Eyes to Evaluate Graft Morphology and Its Association With Visual Outcome. Issue 9 (September 2018) - Graffi, Shmuel; Leon, Pia; Mimouni, Michael; Nahum, Yoav; Spena, Rossella; Mattioli, Leila; Busin, Massimo
Abstract : Purpose: To evaluate the relationship between graft thickness/regularity and visual outcomes of Descemet stripping automated endothelial keratoplasty (DSAEK). Methods: Records of post-DSAEK patients who were examined by anterior segment optical coherence tomography at "Villa Igea" Private Hospital (Forlì, Italy) since April 2015 were reviewed. Pachymetric and elevation maps of both host cornea and graft were analyzed. Graft regularity was determined based on the root mean square error (RMSE) of the graft pachymetric measurements taken 3 and 6 mm from the center and the RMSE of the corneal elevation measurements at its posterior and interface surfaces. These parameters were correlated with best-spectacle-corrected visual acuity (BSCVA) (expressed in logarithm of the minimum angle of resolution) and compared between eyes with central graft thickness (CGT) ≥100 μm (group 1) and eyes with CGT <100 μm (group 2). Results: Eighty-nine post-DSAEK eyes of 89 patients with Fuchs endothelial dystrophy or bullous keratopathy and no significant comorbidities were included. There were 40 eyes (CGT = 138.2 ± 31.7 μm) in group 1 and 49 eyes (CGT = 73.3 ± 15.5 μm) in group 2. The RMSEs of graft pachymetry and the RMSEs of the interface and posterior surface elevation maps at 3 and 6 mm differed significantly between both groups ( P < 0.05). When only eyes with Fuchs endothelial dystrophy (n = 54) were considered in both groups, there was a statistically significant correlation (r = 0.44; P = 0.001) between BSCVA and CGT. Conclusions: DSAEK grafts thinner than 100 μm are more regular than thicker ones. In eyes with Fuchs endothelial dystrophy that are otherwise healthy, thinner grafts yield significantly better BSCVA.